Volume 6: Materials and Fabrication 2020
DOI: 10.1115/pvp2020-21629
|View full text |Cite
|
Sign up to set email alerts
|

Investigation Into Residual Stresses in a Small Bore Pipe Weld With Stacked Stop/Start Locations

Abstract: Small bore austenitic stainless steel pipework is used in a number of nuclear plant systems. Many of these locations are subjected to large thermal shocks and therefore have high fatigue usage factors. Their justification therefore often includes a fatigue crack growth and fracture assessment, for which a key input is the residual stress associated with the welding process, in UK assessments these are typically taken from the R6 compendium. A common process used for these welds is manual tungste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…However, the groups have shown to typically differ regarding their distribution. This implies that variability is a larger concern for thinner-walled pipes (a result consistent with the findings of other authors, [26]); however, more data are required to present alternative treatment of different geometries confidently. It is suggested that less conservative treatment can be used in fracture assessment using the presented results.…”
Section: Resultssupporting
confidence: 89%
“…However, the groups have shown to typically differ regarding their distribution. This implies that variability is a larger concern for thinner-walled pipes (a result consistent with the findings of other authors, [26]); however, more data are required to present alternative treatment of different geometries confidently. It is suggested that less conservative treatment can be used in fracture assessment using the presented results.…”
Section: Resultssupporting
confidence: 89%